Bit‐oriented format extraction approach for automatic binary protocol reverse engineering. Issue 6 (1st April 2016) - Tao, Siyu; Yu, Hongyi; Li, Qing
Abstract : Protocol message format extraction is a principal process of automatic network protocol reverse engineering when target protocol specifications are not available. However, binary protocol reverse engineering has been a new challenge in recent years for approaches that traditionally have dealt with text‐based protocols rather than binary protocols. In this study, the authors propose a novel approach called PRE‐Bin that automatically extracts binary‐type fields of binary protocols based on fine‐grained bits. First, a silhouette coefficient is introduced into the hierarchical clustering to confirm the optimal clustering number of binary frames. Second, a modified multiple sequence alignment algorithm, in which the matching process and back‐tracing rules are redesigned, is also proposed to analyse binary field features. Finally, a Bayes decision model is invoked to describe field features and determine bit‐oriented field boundaries. The maximum a posteriori criterion is leveraged to complete an optimal protocol format estimation of binary field boundaries. The authors implemented a prototype system of PRE‐Bin to infer the specification of binary protocols from actual traffic traces. Experimental results indicate that PRE‐Bin effectively extracts binary fields and outperforms the existing algorithms.